Madame “Paradigm” - V. I. Aleshnikova; G. M. Sundukova (Управление)
The article analyzes the role of the doctor of economic sciences, Professor of Department of theory of management, honored worker of science of the Russian Federation Z.P. Rumyantsev in the development of the theory and practice of the Russian school of management; contribution to the training of the teaching staff. The article provides a wide range of real-world examples, professional characteristics, individual assessment of his joint work with the aspirate and students in the framework of formation and development of the scientific school of management theory. The authors share personal observations and impressions formed in the course of preparation and protection of dissertations on competition of a scientific degree of candidate of economic Sciences under the direct scientific leadership of Zinaida Petrovna Rumyantseva.